Investigation of Teacher Attitudes of Using Information and Communications Technology (ICT) for Pandemic Era - Rizky, Muhammad Hasan (CV. Creative Tugu Pena, 2022)
In 21st century learning, especially teaching, the use of Information and Communications Technology (ICT)is very influential in modifying teaching and learning. Teachers are expected to be able to maximize the use of technology for the benefit of students, especially in classroom learning. This article aims to investigate the attitudes of teachers towards the use of ICT in high grades such as grades 4, 5 & 6, and the challenges faced by teachers in the use of ICT in high grades. This survey was conducted involving 30 high school teachers who teach in primary schools. This article uses a quantitative research design. Respondents demonstrated a positive attitude towards the use of ICT because most of them felt comfortable using ICT as a tool in the teaching and learning process, especially in the current pandemic conditions. In addition, lack of teacher training regarding available computers or software, lack of time to prepare lessons due to other administrative work, insufficient time to master new software or integrate ICT during class periods and lack of support from administrators or colleagues are also challenges faced. by teachers when applying ICT in high grades. This research has implications, namely as a means of communication, managing, integrating, evaluating and creating information in teaching and learning in the classroom. As well as the use of technology in the 21st century in the learning process as well as teaching to achieve students' thinking and learning skills. Keywords: Teacher Attitudes, Teacher Attitude in Pandemic, Online Learning